A Semantic Analysis of Food and Beverage Advertisements on Instagram - I Made Darmayasa Wilantara (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigates the semantic features employed in food and beverage advertisements published on Instagram. The study aims to understand how lexical choices, connotative strategies, and meaning relations are employed to construct brand image, elicit emotional resonance, and influence consumer preferences. Data were collected from ten official advertising posts of popular food and beverage brands that commonly appear on Indonesian users' feeds between January and June 2025. A descriptive qualitative analysis was conducted using frameworks for lexical, connotative, and relational semantics. The findings reveal a consistent pattern: advertisements combine denotative meanings to communicate product attributes, connotative meanings to invoke emotional associations, and relational meanings to assert cultural ties and social identity. These insights demonstrate that semantic strategies are a crucial component of effective digital marketing practice and provide guidance for crafting more persuasive promotional materials. Key words: semantics, advertisement, Instagram, food and beverage, connotative meaning